2020
DOI: 10.1002/wcc.643
|View full text |Cite
|
Sign up to set email alerts
|

Ten years after Copenhagen: Reimagining climate change governance in urban areas

Abstract: In this review, we take stock of the last decade of research on climate change governance in urban areas since the 2009 conference in Copenhagen. Using a systematic evaluation of academic publications in the field, we argue that the current moment of research has been shaped by two recent waves of thought. The first, a wave of urban optimism, which started in 2011 and peaked in 2013, engaged with urban areas as alternative sites for governance in the face of the crumbling international climate regime. The seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 306 publications
(301 reference statements)
0
27
0
Order By: Relevance
“…Although the recommendations above may well be compelling from a conceptual as well as theoretical perspective, the methodological angles of how to examine and overcome power asymmetries in daily resilience building remain ambiguous and the harnessing of scholarly advances for practical achievements challenging. There is an abundance of empirical work that demonstrates how citizen participation in climate resilience decision making can go unquestioned (Castán Broto & Westman, 2020) and how community‐led committees and other seemingly participatory engagements often fail to be inclusive (Koslov, 2019; Woroniecki et al, 2019) or reinforce existing hierarchies across and within scales (Buggy & McNamara, 2016), for instance via elite domination (Córdoba Vargas et al, 2020; McDonnell, 2020). To overcome such pervasive shortcomings, recent methodological advances in resilience scholarship underscore the need to nourish political capabilities and political spaces; the aim is to actively contest exploitative and oppressive power dynamics while mobilizing alternative, emancipatory subjectivities that are needed to negotiate inclusive and equitable resilience in practice and deliberate possible transformative pathways (e.g., Ensor et al, 2021; Matin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although the recommendations above may well be compelling from a conceptual as well as theoretical perspective, the methodological angles of how to examine and overcome power asymmetries in daily resilience building remain ambiguous and the harnessing of scholarly advances for practical achievements challenging. There is an abundance of empirical work that demonstrates how citizen participation in climate resilience decision making can go unquestioned (Castán Broto & Westman, 2020) and how community‐led committees and other seemingly participatory engagements often fail to be inclusive (Koslov, 2019; Woroniecki et al, 2019) or reinforce existing hierarchies across and within scales (Buggy & McNamara, 2016), for instance via elite domination (Córdoba Vargas et al, 2020; McDonnell, 2020). To overcome such pervasive shortcomings, recent methodological advances in resilience scholarship underscore the need to nourish political capabilities and political spaces; the aim is to actively contest exploitative and oppressive power dynamics while mobilizing alternative, emancipatory subjectivities that are needed to negotiate inclusive and equitable resilience in practice and deliberate possible transformative pathways (e.g., Ensor et al, 2021; Matin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Transition management [5][6][7] Structures that nurture niche development, experimental spaces for innovation and learning [8][9][10] Element of niche development embedded in structuration processes Transformative science [11,12] Reflexive learning spaces that combine practice and scientific perspectives [13][14][15][16] Physical research infrastructure…”
Section: General Approach Position Of Rwl Structure Of Rwlmentioning
confidence: 99%
“…"Spillover" here means that the RWL triggered, initiated or influenced any instrument or activity within another mode of governance (e.g., a planning process, a new partnership or an enabling activity). The spillover is then critically scrutinized as to whether it is likely to enhance long-term transformative change or instead cement 'business as usual' [11,29], thus responding to one of the research gaps shown in Section 2 above.…”
Section: Comparative Approach: Thinking Through Elsewherementioning
confidence: 99%
See 1 more Smart Citation
“…Large cities are hotspots of climate impacts and vulnerability, which requires particularly responsible and well-calibrated action (Hunt & Watkiss, 2011). Despite signifi cant progress in urban climate governance over the past decade, it often remains constrained, fragmented and ineffective in regards to the magnitude and scope of the challenges faced by cities, which has led to the context where old, new and emerging frameworks, methods and tools coexist, complement each other, as well as clash and compete (Broto & Westman, 2020).…”
mentioning
confidence: 99%